2018
DOI: 10.3390/met8040215
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Reinforced Magnesium Matrix Composites (Mg/Sic/GNPs): Drilling Investigation

Abstract: Abstract:The machinability of graphene-reinforced magnesium-based hybrid nanocomposites produced through the application of powder metallurgy method has not been completely reported. This article presents an experimental investigation on the thrust force, the surface roughness (R a ), and drilled surfaces characteristics in the drilling process of a Mg/SiC/GNPs (magnesium matrix based silicon carbide and graphene nanoplatelets) hybrid magnesium matrix composite. The hybrid composite material was produced throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…They found that weight fraction, and GNPs average size affect the output responses. Abdulgadir et al [ 25 ] reported an experimental study on the drilling of the Mg-nanocomposite reinforced by 10 wt.% SiC and 0.25 wt.% GNPs. They found that the presence of the GNPs in Mg-nanocomposite reduces the friction between the cutting tool and nanocomposite due to the lubricant effect of graphene resulting in decreasing cutting force.…”
Section: Introductionmentioning
confidence: 99%
“…They found that weight fraction, and GNPs average size affect the output responses. Abdulgadir et al [ 25 ] reported an experimental study on the drilling of the Mg-nanocomposite reinforced by 10 wt.% SiC and 0.25 wt.% GNPs. They found that the presence of the GNPs in Mg-nanocomposite reduces the friction between the cutting tool and nanocomposite due to the lubricant effect of graphene resulting in decreasing cutting force.…”
Section: Introductionmentioning
confidence: 99%
“…This environmentally friendly procedure can be contrasted evaluating the main variables of drilling under specific cutting conditions. Variables such as thrust forces should be low to improve process stability, at least in drilling operations; the literature shows that a homogeneous variation of thrust forces does not exist with respect to cutting conditions, at least in different types of composites such as glass fiber reinforced PEEK [16], fibre metal laminates [17], magnesium matrix based silicon carbide and graphene nanoplatelets (Mg/SiC/GNPs), hybrid magnesium matrix composite [18] or wood-based composite of medium density fiberboard [19]. Nevertheless, the energy consumed during the process could be a key factor to stablish the most sustainable procedure, and also the material removed rate (MRR) in order to evaluate the process efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Chip morphology is reported to be more dominant on cutting speed compared to tool rake angle, volume fraction, and the average size of silicon carbide [ 18 ]. Mustafa et al [ 19 ] conducted drilling studies on graphene nanoplatelet, and silicon carbide reinforced in a hybrid magnesium matrix composite, which was manufactured through the powder metallurgy method. The results of their study showed that lower thrust forces could be achieved using the physical vapor deposition (PVD) coated tool and drilling at a cutting speed of 50 m/min and a feed rate of 0.10 mm/rev.…”
Section: Introductionmentioning
confidence: 99%
“…The results of their study showed that lower thrust forces could be achieved using the physical vapor deposition (PVD) coated tool and drilling at a cutting speed of 50 m/min and a feed rate of 0.10 mm/rev. Their study shows that lower feed rates are preferred while drilling hybrid magnesium metal matrix composites primarily due to the achievement of good surface finish and lower thrust forces [ 19 ]. Dry microdrilling tests were carried out on pure magnesium reinforced with the varying volume fraction of nanoparticles of SiO 2 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%